Efektivitas Metode Muroja'ah dalam Menghafal Al-Qur’an Mahasiswa Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta - Jawad Musyaffa Abdurrahman; Adi Haironi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Education is an integral part of life, inseparable from it, and crucial for any nation to cultivate high-quality human resources in terms of intelligence, spirituality, and general capabilities as the future generation of the nation. All divine messages originate from the Qur’an, perpetually urging humans to realize their potential and existence. The Qur’an serves as a reminder (adz-dzikir), emphasizing that serious reflection upon its teachings enables profound realization and remembrance. This study explores the significance of Quranic memorization, highlighting its preservation within the hearts of believers even amidst adversity. It emphasizes the methodology of Muraja’ah (repetition) as essential in maintaining Quranic memorization, underscoring its role in fortifying recollection and understanding. The research employs a qualitative approach based on primary data from observations supplemented by secondary data from literature review, aiming to comprehensively understand and portray human and social phenomena. This study contributes insights into effective strategies for Quranic memorization, crucial in spiritual and educational contexts, advocating for systematic approaches to sustain and enhance memorization efforts among learners.